Pengembangan Media Permainan Monopoli Pembelajaran Fikih (Mojafi) Pada Materi Salat Jum’at Dan Salat Sunah Di Kelas IV MI - Ersila Devy Rinjani Ersila; Fitria Martanti; Ashilah Khansa Habiba (Jurnal Elementaria Edukasia, 2023)
Learning media is very important for madrasah ibtidaiyah students who are still 7-12 years old on average, where the age vulnerable in the learning process students need learning media that can make it easier to think and understand lessons. This research was conducted with the aim of knowing the needs, validity, and effectiveness of fiqh learning media (mojafi) on the material of Friday prayers and sunnah prayers in class IV MI Permata Belia. The media development model uses ADDIE (Analysis, Design, Development, Implementation, Evaluation). The validity of the mojafi game material based on the results of the material expert validator assessment with a percentage of 96% or very valid. The validity of the mojafi game media based on the results of the assessment of media expert validators with a percentage of 84% or very valid. The effectiveness of getting the results of the average value of the pre-test 58.71 and post-test 89.63. Based on calculations using the normality test, the sample is normally distributed, t-test Sig. (2-tailed) 0.00 and the N-Gain Test obtained an average result of 0.76 with a percentage of 76% so that it entered the effective category and the response of students obtained a result of 88% in the very good category.